Exploratory and confirmatory factor analysis of PERMA for Indonesian students in mathematics education programmes (Tiriamoji ir patvirtinamoji indonezijos studentų psichologinės gerovės (PERMA) faktorinė analizė matematikos mokymo programose) - Hidayat, Riyan; Habibi, Akhmad; Saad, Mohd Rashid Mohd; Mukminin, Amirul; Wan Idris, Wan Izani (Vytautas Magnus University Education Academy, 2019)
This study examined the validity and reliability of PERMA instruments to determine the nature of PERMA for Indonesian students in mathematics education programmes. A total of 274 students participated, selected by using cluster random sampling. A survey design was employed to investigate the factor structure of the PERMA. Quantitative data were analysed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) using SPSS 23 and AMOS 18. EFA revealed similar structures from prior research and the present study. The CFA approach verified the questionnaire of PERMA was satisfactory for Indonesian students’ context. This work concludes the PERMA of Indonesian university students have a five-factor structure. These findings imply the greater importance of validating and confirming the structure of students’ PERMA relative to translating a construct into a different language.